Outcomes of Kahook Dual Blade Goniotomy for Uveitis Associated Open Angle Glaucoma or Ocular Hypertension. Issue 11 (9th November 2022) - Miller, Victoria J.; Patnaik, Jennifer L.; Young, Cara E. Capitena; SooHoo, Jeffrey R.; Seibold, Leonard K.; Kahook, Malik Y.; Ertel, Monica K.; Palestine, Alan G.; Pantcheva, Mina B.
Abstract : Précis: Kahook Dual Blade (KDB) goniotomy can successfully lower intraocular pressure in some patients with uveitis-associated ocular hypertension or glaucoma. Purpose: The purpose of this study was to report a case series of patients that underwent KDB goniotomy at a single institution for uveitis-associated ocular hypertension or glaucoma with an open angle. Methods: We performed a retrospective chart review of all patients with uveitis-associated ocular hypertension or glaucoma who underwent KDB goniotomy with trabecular meshwork excision alone or in combination with phacoemulsification cataract surgery at a single center between August 2017 and February 2020. The case series included 45 eyes of 37 patients. All eyes developed ocular hypertension refractory to maximum-tolerated medical therapy and required surgical intervention. Two eyes were excluded as they were lost to follow-up before 5 months postoperatively. Surgical success was defined as reaching the goal intraocular pressure or lower for each patient, including ongoing medical therapy. Results: At most recent follow-up, 25 (55.6%) of 45 eyes had an intraocular pressure that was at goal. Mean follow-up time was 15.2±12.1 months ranging from 0.5 to 36 months postoperatively, considering that patients were eliminated from the data analysis once they required a second surgery. The mean number of preoperative medications, including oral carbonic anhydrase inhibitors was 3.7±1.2 medications. The mean number of postoperative medications through the last clinic visit was 2.5±1.9 medications for a mean reduction of 1.2±1.6 medications ( P -value <0.0001*). Conclusions: This larger case series shows that some patients with uveitis-associated ocular hypertension or glaucoma with an open angle may have success with KDB goniotomy.